Modeling Temperature Control System with Sensor Response Time using Differential Difference Equations (Journal of Advances and Scholarly Researches in Allied Education, 2026)
In this experiment, differential difference equations are used to model temperature control systems with sensor response times. It contrasts the Runge-Kutta Method (Order 4), the Improved Euler's Method (Heun's Method), and Scipy's solve_ivp function, four numerical techniques. The study emphasizes how crucial it is to characterize sensor response time because it serves as the basis for precise simulations and control schemes. The Euler's Method is renowned for its speedy computations but has mediocre accuracy and stability. The Runge-Kutta Method (Order 4) offers excellent accuracy and stability at the expense of a higher computing cost, while the Improved Euler's Method strikes a balance between simplicity and accuracy.The solve_ivp function in Scipy provides a high-level user interface with sophisticated capabilities, although it might have a little more processing overhead. For realistic simulations and efficient control techniques, accurate modeling of temperature control systems with sensor response time is essential.